Tracing Gender Perspectives in Literature: The Search for Islamic Feminism in Faith and the City by Hanum Rais - Sistiadinita Sistiadinita (English Language in Focus (ELIF), 2023)
This is the study with a concern to reinterpret the feminist ideas on an autobiographical fiction written collaboratively by Islamic woman author, Hanum Rais and her husband, Rangga Almahendra. Taking Faith and The City as the studied material, this study aims to investigate the occurrence of gender identity, traditional gender roles and stereotypes of Asian Muslim men and women in United States and how the story reflects the woman’s struggle in choosing between domestic responsibilities and aspiring career and the man’s struggle in maintaining his relationship without losing their Islamic identity. The method of this study is close reading by identifying gender identity, traditional gender roles and stereotyping of male and female character and representation of man and woman struggle following the Islamic values.  Based on the findings, the researcher concluded that both characters represent struggle of husband and wife who return to Islamic teachings and uphold the values taught by the Qur'an and Hadith to reach gender equity. Both figures tend to making adjustment for giving contribution to public spheres without leaving their faith and values by adhering to the gender role and gender identity and breaking the negative stereotypes surrounding the Islamic couple.